2020
DOI: 10.1186/s12936-020-03258-w
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the durability of the long-lasting insecticidal nets Olyset® and PermaNet® 2.0 in similar use environments in Zanzibar

Abstract: Background: Malaria transmission in Zanzibar has dramatically reduced in recent years but vector control interventions such as long-lasting insecticidal nets (LLIN) must continue to reach malaria elimination. To achieve this, the Zanzibar Malaria Elimination Programme needs actionable evidence of the durability of the LLIN brands distributed. This study compared physical and insecticidal durability of two LLIN brands: Olyset ® and PermaNet© 2.0 in two similar districts on the islands of Unguja and Pemba. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 20 publications
2
25
3
Order By: Relevance
“…The median survival time reported in our study is higher than similar studies conducted in Africa that have also evaluated PermaNet ® 2.0 LLINs. In Tanzania the estimated survival was 2.5 years, in Zanzibar it was 3.1-3.3 years and in Zambia it was 2.5-3 years (Haji et al, 2020;Lorenz et al, 2019;Tan et al, 2016). In our study, the physical integrity of the LLINs-a key component for the functional survivorship-was high in each of the survey timepoints (range: 84-94%), whereas other studies have reported lower values (e.g.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The median survival time reported in our study is higher than similar studies conducted in Africa that have also evaluated PermaNet ® 2.0 LLINs. In Tanzania the estimated survival was 2.5 years, in Zanzibar it was 3.1-3.3 years and in Zambia it was 2.5-3 years (Haji et al, 2020;Lorenz et al, 2019;Tan et al, 2016). In our study, the physical integrity of the LLINs-a key component for the functional survivorship-was high in each of the survey timepoints (range: 84-94%), whereas other studies have reported lower values (e.g.…”
Section: Discussioncontrasting
confidence: 51%
“…In our study, the physical integrity of the LLINs-a key component for the functional survivorship-was high in each of the survey timepoints (range: 84-94%), whereas other studies have reported lower values (e.g. 68% at 36 months) (Haji et al, 2020). These differences are further highlighted by the median total hole area, which in our study was only 34 cm 2 at 32 months, whereas other studies evaluating PemaNet ® 2.0 LLINs reported values of 390 cm 2 and 106 cm 2 (Craig et al, 2015; Vanden Eng et al, 2015).…”
Section: Discussioncontrasting
confidence: 49%
“…Field evidence increasingly shows that current ITNs do not last as long as expected under real use settings, and that there is a wide variation in both bio-efficacy and durability in different settings [181][182][183][184]. In one study in Tanzania, scientists examined the durability of ITNs distributed by the government between 2009 and 2011 in eight districts [185].…”
Section: Importance Of Durability and Functional Survival Of Nets In mentioning
confidence: 99%
“…NetProtect® was two times more likely to be serviceable when compared to Olyset® in this setting. When compared to PermaNet®, Olyset® nets have been observed to have more holes in both Mozambique [46], Zambia [47] and Zanzibar [48] and mainland Tanzania [32]. In Madagascar [49], 55.6% of NetProtect® ITNs were in good condition after a year when compared to Royal Sentry® (56.8%) and Yorkool® (69.2%), which is lower than in the current study, indicating the importance of considering location when estimating ITN durability as cultural in uences, net care and attitudes as well as the physical environment all impact on the expected life of ITNs.…”
Section: Discussionmentioning
confidence: 97%